Peranan sensory marketing sebagai prediktor revisit intention melalui customer emotions di Railway Coffee - Felix Fernando; Fransisca Mulyono (Jurnal Manajemen Maranatha, 2023)
Sensory marketing is a marketing strategy that uses sensory experiences to attract potential customers. The purpose of this study was to determine the effect of sensory marketing on revisit intention through customer emotions. The method is explanatory-causal with a quantitative approach using SEM (Structural Equation Modeling). The number of respondents in this study amounted to 233 people who had come to Railway Coffee at least once. Data was collected using a questionnaire via online survey and using non-probability sampling. This study concludes that sensory marketing has an effect on customer emotions, customer emotions have an effect on revisit intention, sensory marketing has an effect on revisit intention through customer emotions, whereas sensory marketing has no effect on revisit intention.